Diurnal variation of outgoing longwave radiation derived from I NSA T-I B data - KELKAR, R. R.; RAO , A.V. R. K.; PRASAD, SANT (MAUSAM, 1993)
In this paper, 3-hourly values of Outgoing Long wave Radiation (OLR) for the years 1987 .to 1990 over the Indian Ocean region, derived from’1NSAT-IB VHRR observations, have been used to study the patterns of diurnal variation of OLR. The nature of the diurnal variations over different regions such as desert, ocean, monsoon area and equatorial trough in four representative months of the year is discussed. The variations in the diurnal range of OLR and the hours of occurrence of OLR minimum and maximum, are also presented.Daily means of TNSAT OLR using all.eight 3-hour samples and four different pairs of. 12-hour samples were computed. Results show that they are highly correlated. However, averages made with OLR values corresponding to 0230 and 1430 local time are slight underestimates compared to the 8-sample averages, whereas averages based upon 0830 and 2030 local time are slight overestimates.